Analisis Program Keluarga Harapan (PKH) dalam Meningkatkan Taraf Hidup Keluarga Penerima Manfaat (KPM) di Nagari Tanjung Beringin Selatan Kabupaten Pasaman - Lisa Ardianto; Dewi Manda Angraini (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to determine the effect of the Family Hope Program in improving the standard of living of beneficiary families (KPM). This research is motivated by the community in the South Tanjung Beringin subdistrict who are still unable to meet their daily needs. This has an impact on their children's education and the people in Kenagarian still do not feel fully prosperous. The research method is qualitative through a descriptive approach that describes something as it is, this research was carried out directly in the field to conduct direct interviews with the community receiving PKH assistance and PKH assistants.